Daiva Varṇāśrama dharma and the formation of modern Vaiṣṇava subjects in the International Society for Krishna Consciousness, Mumbai - Robinson, Claire C. (Nidān, 2016)
As inheritors of a transnational, institutionalized Vaiṣṇava tradition, the Indian members of ISKCON's Chowpatty Mumbai temple community negotiate their strict religious practice within Mumbai's globalized cityscape. Their community has developed oases of religious training centered on the practice of daiva varṇāśrama dharma, described in community literature as a "Vedic system of social organization with a spiritual perspective". This revisioned approach to vaidika Vaiṣṇava ethics takes shape in a community-wide network called the Counselling System, aimed at training ethical selves to embody a model of Vaiṣṇava bhakti. Chowpatty's Counselling System provides a space for the cultivation of an alternative modernity-applying tropes of self-care and legitimizing discourses of education to a renewed construction of Vaiṣṇava community. My article will explore dharma as an interpretative category in Chowpatty's Counselling System, through analysis of training manuals and public courses produced for Mumbai's upper and middle class residents.